Concussions in Ice Hockey: Is it Time to Worry? - Amin, Khizer (The Meducator, 2012)
Recent events have highlighted the issue of concussions in sports, particularly in ice hockey. A concussion is an injury to the brain caused by acceleration forces imparted on the brain. Symptoms vary in severity from confusion and minor headaches to loss of consciousness and amnesia. Concussions are a common sports injury that have been associated with neurological and psychiatric impairment, and second-impact syndrome may even lead to death. The serious nature of these injuries has evoked calls from the scientific community to make hockey a safer game by modifying current rules and regulations. This Critical Review summarizes recent research on concussions and discusses the implications in the context of sports.